Some Economic Applications of Differential Equations - Akmal I. Sotvoldiyev; Akmal I. Sotvoldiyev (Academia One Publishing, 2023)
Applications of differential equations are now used in modeling motion and change in all areas of science. The theory of differential equations has become an essential tool of economic analysis particularly since computer has become commonly available. It would be difficult to comprehend the contemporary literature of economics if one does not understand basic concepts (such as bifurcations and chaos) and results of modem theory of differential equations.
Keywords: model; stock; prices